Analisis Perbandingan Kinerja Struktur Gedung Akibat Penurunan Mutu Beton pada Proyek di Wilayah Lombok - Achmad Fadli Erlangga; Rizqi Alghiffary (JURAL RISET RUMPUN ILMU TEKNIK, 2026)
This study analyzes a 10-floor multi-story lecture building in Lombok, focusing on the impact of concrete quality degradation on the building's performance. Due to limited material access, the actual on-site concrete quality changed from the design quality of fc 30 MPa to fc 24.9 MPa. The building structure was modeled in 3D using ETABS v22 software, and two structural models were compared: one with the design concrete quality (fc' 30 MPa) and one with the actual quality (fc' 24.9 MPa). The analysis evaluated dynamic performance, inelastic displacements, P-Delta effects, and reinforcement requirements. The comparison aimed to assess the impact of concrete degradation on structural stiffness, inter-story displacements, and reinforcement needs. The results show that concrete quality deterioration increases the structure's vibration period, inelastic displacement, and lateral forces due to P-Delta effects. While beam reinforcement requirements remain mostly unchanged, column reinforcement significantly increases, especially in columns with large axial forces. This study provides valuable insights into the technical consequences of concrete quality degradation and serves as a reference for evaluating structural redesigns in projects facing material limitations.